Organizing Volkswagen: A Critical Assessment. Issue 3 (9th September 2016) - Brooks, Chris
Abstract : The union organizing drive in Chattanooga has a number of unique features that make the campaign deserving of close examination: an employer on whose board labor holds half the seats and maintains a formal corporate commitment to worker voice and participation, a degree of employer neutrality that cannot be expected at any other foreign automaker, and what was likely the largest and most expensive anti‐union campaign ever waged by third‐party groups. This article highlights those lessons from the UAW's organizing campaign at Volkswagen that are likely to be prescient to future organizing drives. In doing so, I provide an overview of Volkswagen as a company, the UAW's organizing campaign from its beginning in 2013 to the present day, and a detailed discussion of the UAW's strategic mistakes. Most importantly, I detail the actual concerns, interests, thoughts, and reflections of rank‐and‐file workers at Volkswagen.